Which is More Effective: The Carrot or the Stick? Environmental Policy, Green Innovation and Enterprise Energy Efficiency–A Quasi-Natural Experiment From China - Wang, Yuan; Hu, Jiali; Hu, Yi; Wang, Yu (Frontiers in Environmental Science, 2022)
As the concept of carbon neutralization is valued, attention is paid to how environmental protection policies affect enterprises. However, little is known about how environmental policies affect enterprise energy utilization efficiency and green innovation. This paper proposes that incentive environmental protection policy (environmental protection incentive) and punitive environmental protection policy (environmental protection regulation) have different impact mechanisms on enterprise green innovation and energy utilization efficiency. By using the data of listed enterprises since the implementation of the new environmental protection law in China and using PSM-DID method to construct a quasi natural experiment, the following conclusions are drawn. 1. Environmental protection incentives are not conducive to enterprises to improve energy utilization efficiency; 2. Environmental protection regulation can improve enterprise energy utilization efficiency; 3. Environmental protection incentives are not conducive to green innovation; 4. Environmental protection regulation is conducive to green innovation of enterprises; 5. Green innovation plays a complete intermediary role in the relationship between environmental protection policies and enterprise energy utilization efficiency; 6. Different policies have heterogeneity on Enterprises: environmental protection incentives are conducive to the improvement of energy utilization efficiency of state-owned enterprises, but not conducive to non-state-owned enterprises; The effect of environmental protection regulation on non-state-owned enterprises is stronger than that of state-owned enterprises. This study compares the impact of different environmental protection policies on enterprise green innovation and energy utilization efficiency, and puts forward more effective and realistic targeted policy suggestions. This paper tries to understand the mechanism of policy through comparison; The government has made contributions to promoting green innovation, efficient and clean production by implementing policies for enterprises.